2007
DOI: 10.1200/jco.2007.25.18_suppl.580
|View full text |Cite
|
Sign up to set email alerts
|

Are BRCA1 mutations a predictive factor for anthracycline-based neoadjuvant chemotherapy response in triple-negative breast cancers?

Abstract: 580 Background: BRCA1 being involved in DNA repair and apoptosis, its mutations may influence response to chemotherapy. In vitro studies demonstrated that loss of BRCA1 function increased sensitivity to platinum compounds and induced resistance to anthracyclines. BRCA1-related breast cancers tend to be ductal carcinomas with high tumor grade, absence of hormonal receptors and no HER2 overexpression, so called triple-negative. We retrospectively analyzed anthracycline-based neoadjuvant chemotherapy efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, Hubert et al [ 68 ] and Wong Wong Keet et al [ 71 ] observed worse outcomes in BRCA2 vs. BRCA1 carriers. The data of Petit et al [ 72 ] are in strong disagreement with the above observations: in their study only 2/12 (17%) of BRCA1 carriers receiving 5-fluorouracil, epirubicin and cyclophosphamide achieved pathologic complete response (pCR), while pCR was detected in 21/43 (49%) sporadic triple-negative BC.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, Hubert et al [ 68 ] and Wong Wong Keet et al [ 71 ] observed worse outcomes in BRCA2 vs. BRCA1 carriers. The data of Petit et al [ 72 ] are in strong disagreement with the above observations: in their study only 2/12 (17%) of BRCA1 carriers receiving 5-fluorouracil, epirubicin and cyclophosphamide achieved pathologic complete response (pCR), while pCR was detected in 21/43 (49%) sporadic triple-negative BC.…”
Section: Introductionmentioning
confidence: 89%